LINGUISTIC EXPRESSION OF GENDER DISTINCTIONS IN ENGLISH PROVERBS AND SAYINGS - Karapetyan, Lili; Danukhyan, Lusine (Armenian Folia Anglistika, 2023)
The present study aims at investigating the linguistic expression of gender distinctions in English proverbs and sayings through the lens of paremiology. The investigation focuses on the classification of English proverbs and sayings according to their respective gender component. Our research hypothesis posits that proverbs and sayings, as forms of verbal folklore, have traditionally ascribed specific human traits and activities to individuals based on their gender. To test this hypothesis, over four hundred English proverbs and sayings have been analyzed. The methodology employed in the paper is based on historical research methods, which involve collecting and analyzing information in order to explain past phenomena. The analysis has also employed the data grouping method to organize proverbs and sayings into relevant categories. The data collection has utilized both primary and secondary sources of information. Primary sources include reviews and scientific articles, while in secondary sources are include encyclopedias and dictionaries of proverbs and sayings. The results show that proverbs and sayings reflect gender stereotypes and societal divisions which are often difficult to break. However, the deeper understanding of the ways in which gender roles have been constructed and perpetuated throughout history, can identify areas in which progress towards gender equality is made.
Keywords: paremiological unit; proverbs; sayings; folklore; gender component